Pengaruh Media Sosial Terhadap Motivasi Belajar Siswa di SMP Negeri 12 Kota Tidore Kepulauan - Samili, Asnita Ode; Adjam, Syarifuddin; Ibrahim, Fitriana; Hasim, Jainudin (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This article examines the use of social media to support the learning process at SMP Negeri 12 Tidore Islands City. This research aims to determine the influence of social media on student learning motivation. The method used in this research is descriptive qualitative, data collection techniques are interviews, observation and documentation. The results of this research found that the use of social media really supports learning at SMP Negeri 12 Tidore Islands City, students are very enthusiastic in collaborating on teaching materials with online media, students are more enthusiastic about following online tutorials, students find it easier to learn, teachers are providing education to students to use social media wisely, with social media, teachers and students can interact in learning activities anywhere and at any time. In this way, educational interactions are created between students and teachers which can strengthen student motivation so that students have a sense of enthusiasm for studying more actively. So that the use of social media will have an impact on students as a good communication medium. This method of using social media can be used as initial capital to increase effective educational communication between teachers and students as well as educating students. Moreover, if other subject teachers also do the same thing to build closeness with students and direct students to educational communication that takes place outside of school learning hours. The conclusion of this research is that the use of social media in learning at SMP Negeri 12 Tidore Islands City is going very well so that students